Peran Orang Tua Terhadap Permainan Gadget di Dusun Tahoku - Sintia Haryati Bahar; Agustinus Soumokil; Titus Gaite (Peneliti.net, 2023)
The impact of using gadget games on children's learning hours is an indicator that cannot be avoided, does it affect children's learning hours, or on the contrary makes children even lazy to study, because they are carried away by content on gadgets that satisfy children in terms of entertainment, children's learning hours become not conducive, children become aggressive because they feel their need for entertainment is not met if their parents limit it. Therefore, there must be reciprocity between parents and children. Described in general, the purpose of this research are (1). What is the positive impact of using gadgets on children's study hours at home. (2). What are the negative impacts of using gadgets on children's character and morals? This study uses a qualitative descriptive analysis approach where data is taken and collected through the process of observation, interviews and documentation. The results of this discussion show that the children that the researchers encountered in the field have experienced moral and character degradation, this is of course apart from the responsibilities of parents in educating and controlling children in giving gadgets. Children who go too far in using these gadgets have formed a degenerate moral order, this can be seen from the way children behave. The more he opens his mind, the more he will practice his findings on his gadget. As a result, children start not respecting their elders, their lives are pragmatic, everything depends on gadgets, it's hard to think big because of their attachment to gadgets, that's why the role of parents is needed in supervising the use of gadgets in children, so that children children are not mistaken for the negative things from the gadget itself.